Pemujaan Dewa-Dewa Lokal Dalam Pelaksanaan Saṃskāra Di Desa Pedawa Buleleng Bali - Putu Maria Ratih Anggraini; I Nyoman Suka Ardiyasa (Kamaya: Jurnal Ilmu Agama, 2021)
The worship of local gods in the implementation of Saṃskāra in the Pedawa Village community is seen in the Sesapa spoken by Balian Desa in the implementation of the ritual. Not only local gods but worship of places and temples in Pedawa Village is also carried out. This study questions the worship of local gods that was carried out during the implementation of Saṃskāra in Pedawa Village. The method used in this research is descriptive qualitative. Data was collected by using interview and direct observation techniques. The results of this study show that the worship of local gods in the implementation of Saṃskāra in Pedawa Village can be divided into 4, namely (1) worship that is specifically shown to local gods, namely worship of gods who are believed by the Pedawa people to provide salvation as Ida Pengkan Prataksu , Ida Gede Kemulan, Rai Ida. (b) special worship for places in Pedawa Village such as Gunung Sari Pedawa, In Kamulan Bingin, Telaga Waja Pengampelan and other places in Pedawa Village (c) worship of holy places in Duurin Capah, namely worship of temples in the Tamblingan and Buyan Areas or known as Dalem Tamblingan Village Chess such as Ulun Danu Tamblingan Temple, Dalem Naga Loka, Sang Hyang Kangin, Dangin Capah taler ring Steaming. (d) worship of sacred places in Segara, namely the worship of the Labuan Aji Temple which is believed by the Duwuran Capah community to be a very important temple on the coast of the North Coast of Bali.